Al-Mukhatarah al-Akhlaqiyyah fi al-Istithmar fi al-Musyarakah Allati Tajriha al-Masarif al-Islamiyyah - Hammad, Hamzah Abd al-Karim (Jurnal Fiqh, 2010)
One of the most remarkable principles that Islamic banks were established for is seeking to develop communities economically. The practical implementation of this aim is represented in activating investment forms that will actualize this. One of these forms is ?Musharakah?, nevertheless, the actual reality of many Islamic banks shows the weakness of investment in this form. One of the most important reasons that made Islamic banks not to implement this form is ethical values risks, such as investor?s trustworthiness and his morals. Therefore, this study aims at demonstrating this risk both in fiqh and banking and attempts to show fiqh and banking solutions for it . The study uses a descriptive reasoning approach and managed to construct a clear banking approach to minimize this risk. As for fiqh solutions for this phenomenon, it centers about to what extent there is a possibility of imposing responsibility as a condition on partner . The study concludes that this condition is not permissible and it recommends making more researches about obstacles that get in the way of activating investing forms and also trying to put real, factual solutions for them.